2022
DOI: 10.1038/s41392-022-01198-2
|View full text |Cite
|
Sign up to set email alerts
|

A PD-L1-targeting chimeric switch receptor enhances efficacy of CAR-T cell for pleural and peritoneal metastasis

Abstract: Pleural and peritoneal metastasis accompanied by malignant pleural effusion (MPE) or malignant ascites (MA) is frequent in patients with advanced solid tumors that originate from the lung, breast, gastrointestinal tract and ovary. Regional delivery of CAR-T cells represents a new strategy to control tumor dissemination in serous cavities. However, malignant effusions constitute an immune-suppressive environment that potentially induces CAR-T cell dysfunction. Here, we demonstrated that the anti-tumor cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…PD-L1 axis is a key immunosuppressive signal provided by tumor cells and MDSCs in TME, which limits CAR-T cell function. Some studies designed the CAR-T cells secreting anti-PD-L1 single-chain variable fragment (scFv) or generated a novel PD-L1-targeting chimeric switch receptor (PD-L1.BB CSR) (165)(166)(167). The former CAR-T cells secreting anti-PD-L1 scFv which could bind to PD-L1 on PD-L1 high tumor cells and MDSCs competitively and block their binding with anti-PD-L1 monoclonal antibodies, leading to increased efficacy (165).…”
Section: Engineering Car-t Cells To Deliver the Targeting Agents Agai...mentioning
confidence: 99%
See 1 more Smart Citation
“…PD-L1 axis is a key immunosuppressive signal provided by tumor cells and MDSCs in TME, which limits CAR-T cell function. Some studies designed the CAR-T cells secreting anti-PD-L1 single-chain variable fragment (scFv) or generated a novel PD-L1-targeting chimeric switch receptor (PD-L1.BB CSR) (165)(166)(167). The former CAR-T cells secreting anti-PD-L1 scFv which could bind to PD-L1 on PD-L1 high tumor cells and MDSCs competitively and block their binding with anti-PD-L1 monoclonal antibodies, leading to increased efficacy (165).…”
Section: Engineering Car-t Cells To Deliver the Targeting Agents Agai...mentioning
confidence: 99%
“…The former CAR-T cells secreting anti-PD-L1 scFv which could bind to PD-L1 on PD-L1 high tumor cells and MDSCs competitively and block their binding with anti-PD-L1 monoclonal antibodies, leading to increased efficacy (165). The latter CAR-T cells can bind to PD-L1, switching the inhibitory signal into an additional 4-1BB signal, displayed superior fitness and enhanced functions in culture medium, causing rapid and durable eradication of pleural and peritoneal metastatic tumors in xenograft models (166). Furthermore, a phase I clinical trial related to this study, was initiated in patients with pleural or peritoneal metastasis (NCT04684459).…”
Section: Engineering Car-t Cells To Deliver the Targeting Agents Agai...mentioning
confidence: 99%
“…By merging inhibitory signals with immune-activating signals, these fusion receptors play a crucial role in enhancing the functionality of T cells within the challenging tumor microenvironment. In a recent study, it was demonstrated that CAR-T cells targeting HER2 and coexpressing CSR specific for PD-L1 exhibited superior fitness and enhanced functions in xenograft models (Ma et al 2022 ). Further investigations revealed upregulated expression of genes associated with T-cell activation, proliferation, and cytotoxicity in these CAR-T cells.…”
Section: Strategies For Overcoming the Immunosuppressive Tumor Microe...mentioning
confidence: 99%
“…Such studies accentuate the importance of PD-L1 in solid tumors, especially ovarian cancer. In 2022, Ma and colleagues reported that the tumoricidal efficacy of 2 nd generation HER2-redirected CAR-Ts was hampered by the component of malignant pleural effusion (MPE) or malignant ascites (MA), leading to a compromised expansion and cytokine production ability of the CAR-Ts ( 74 ). These researchers investigated the reason for this occurrence and identified a high-level expression of PD-L1 by the cells of MPE/MA for this negative impact ( 74 ).…”
Section: Target Antigens For Ovarian Cancer Car-t Therapymentioning
confidence: 99%